Usability Testing and User Interface Improvement of Mobile Banking Application: Livin’ by Mandiri - Alfaridzi, Mohamad Gilang; Hanggara, Buce Trias; Az-zahra, Hanifah Muslimah (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2023)
Livin' by Mandiri is a mobile banking application that is integrated with Bank Mandiri banking services and its digital ecosystem. However, some users reported negative responses regarding usability aspects. This study aimed to determine the usability problems faced by users, measure the level of usability, and recommend the user interface design for usability improvement. The evaluation was carried out using the Usability Testing method which collected quantitative and qualitative data. Quantitative data was collected by measuring usability metrics data gathered while participants worked on task scenarios and filled out questionnaire. Meanwhile, qualitative data is collected through interviews with participants to gain insight from users on usability issues. The evaluation of the existed application show that the value of the learnability aspect was 68%, the efficiency was 0.013189 goals/sec, the error was 33.28% and the satisfaction aspect score was 73.5 (good). Participants said that the difficulties they faced most were features or menus that were difficult to find or unknown. Next, recommendations were construct to solve the problem by implementing usability guidelines. The user interface design recommendations were manifested in a high-fidelity prototype. The prototype was also evaluated with the usability testing method. The prototype evaluation showed an improvement of usability. The learnability aspect increased to 93%, the efficiency aspect increased to 0.026295 goals/sec, the error decreased to 2.34%, and the satisfaction aspect score was 84.4 (excellent).